STRATEGI PENGEMBANGAN DESA WISATA CIBEUREUM SEBAGAI DESTINASI WISATA PREMIUM - Sri Mulyati; Agus Irpan Nurhidayat; Siti Fadjarajani; Cahya Darmawan (Pringgitan, 2025)
The development of premium tourism villages is an innovative strategy in the tourism industry that prioritizes quality of services, environmental desires, and exclusive experiences for tourists. Cibeureum Tourism Village in Sukamantri District, Ciamis Regency has great potential to become a premium tourist destination by relying on natural beauty, cultural heritage, and active community participation. This study uses qualitative descriptive approachers with case study methods to analyze the development strategy of premium tourism villages. The results of the study show that the success of the development of Cibeureum Tourism Village is highly dependent on aspects of attraction, accessibility, amenities, quality services, and branding. In addition, the support of the government, historians, tourism industry players, and digital marketing optimization are key factors in increasing the competitiveness of this destination. With the implementation of the right strategy, Cibeureum Tourism Village has the potential to become a sustainable model of premium tourism village and have a positive impact on the economy, social, and environment of the local community.